Edukasi Pemberian Tablet Tambah Darah pada Ibu Hamil Sebagai Upaya Pencegahan Stunting - Anita, Anita; Aprisalana, Aprisalana; Windasari, Desy; Sofiati, Zulfiana; Asmawariza, Lalu Hersika (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2026)
Stunting remains a major public health problem globally and in Indonesia, particularly during the first 1,000 days of life. One of the main risk factors for stunting is maternal anemia caused by iron deficiency during pregnancy. Although the government has implemented an iron supplementation program (Tablet Tambah Darah/TTD), its implementation at the primary health care level is often not accompanied by structured educational evaluation. This community service activity aimed to describe the effectiveness of structured education on iron tablet consumption in improving pregnant women’s knowledge as a preventive effort against anemia and stunting. The activity was conducted at Tekad Jaya Integrated Health Post (Posyandu), Selagik Village, under the working area of Puskesmas Rarang, on November 15, 2025, involving 15 pregnant women. A pre-experimental one group pre-test and post-test design was applied. Education was delivered through interactive lectures and discussions using leaflets and the Maternal and Child Health (MCH) handbook. Knowledge was measured using a 10-item questionnaire before and after the intervention. Scores were converted to a 0–100 scale and categorized as good (80–100), moderate (50–70), and poor (<50). The mean pre-test score was 58.7 (range 40–70), with 93.3% of participants categorized as moderate and 6.7% as poor. After the educational intervention, the mean post-test score increased to 95.3 (range 80–100), and 100% of participants achieved the good category. The average increase in knowledge score was 36.6 points. These findings indicate that structured education at the posyandu level improved pregnant women’s knowledge regarding iron tablet consumption and its role in preventing anemia and stunting. Integrating routine, measurable educational activities into primary health services may strengthen maternal awareness and support stunting prevention efforts at the community level.